Solid-state electrolyte, all-solid-state battery including the same, and its manufacturing method

KR103018733B1Active Publication Date: 2026-09-11EBS SQUARE INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020240043522
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2026-09-11
Estimated Expiration
2044-03-29

Smart Images

  • Figure 112024035602220-PAT00002_ABST
    Figure 112024035602220-PAT00002_ABST
Patent Text Reader

Abstract

A solid electrolyte according to one embodiment comprises an oxide-based solid electrolyte; and a dopant doped into the oxide-based solid electrolyte, wherein the dopant may include a GQD (Graphene Quantum Dot).
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a solid electrolyte with improved ion conductivity and visible light transmittance, an all-solid-state battery including the same, and a method for manufacturing the same. Background Technology

[0002] Lithium-ion batteries (LIBs) have become an essential energy storage medium in portable electronic devices, electric vehicles, and various industrial applications due to their superior energy density and rechargeability. These batteries are widely used alongside technological advancements because of their ability to efficiently store electrical energy and rapidly release it when needed.

[0003] Conventional lithium-ion batteries carry the risk of thermal runaway and explosion due to the use of highly flammable organic liquid electrolytes. These safety issues act as a significant obstacle limiting the use and application range of batteries, and the development of all-solid-state batteries (ASSBs) based on solid electrolytes is attracting attention as an alternative approach to address this.

[0004] All-solid-state batteries offer significantly higher safety than LIBs by eliminating the risk of ignition and explosion caused by electrolyte decomposition reactions or the use of flammable organic solvents. This is made possible by the use of solid electrolytes, which are non-flammable and exhibit high thermal and electrochemical stability against mechanical stress (e.g., cutting, bending). Among these solid electrolytes, oxide solid electrolytes, in particular, contribute to improving the performance of all-solid-state batteries by providing high ionic conductivity and chemical stability, and can be applied to various solid electrolyte applications.

[0005] Furthermore, because all-solid-state batteries do not contain flammable organic solvents due to the use of solid electrolytes, safety devices can be simplified, offering advantages in terms of manufacturing costs and productivity. As such, all-solid-state batteries utilizing solid electrolytes play a crucial role in overcoming the shortcomings of conventional lithium-ion batteries and providing safer and more efficient energy storage solutions. The problem to be solved

[0006] The present embodiment aims to provide a solid electrolyte and an all-solid-state battery in which ion conductivity is enhanced through doping of a dopant into the solid electrolyte.

[0007] The present embodiment aims to provide a solid electrolyte and an all-solid-state battery that can be utilized in various fields by securing a transmittance of visible light above a certain level.

[0008] The present embodiment aims to provide a solid electrolyte and an all-solid-state battery that can be utilized in various fields by having flexible properties.

[0009] The present embodiment aims to provide a solid electrolyte and an all-solid-state battery that can produce high-density pellets in a short sintering reaction time and are advantageous for mass production processes. means of solving the problem

[0010] A solid electrolyte according to one embodiment comprises an oxide-based solid electrolyte; and a dopant doped into the oxide-based solid electrolyte, wherein the dopant may include a GQD (Graphene Quantum Dot).

[0011] The above dopant may be provided with a weight of 5% or more and less than 20% based on 100 parts by weight of the oxide-based solid electrolyte.

[0012] The above solid electrolyte may be provided with a transmittance of 18 to 38% for visible light of 400 to 700 nm as measured by a UV-vis spectrophotometer.

[0013] The above solid electrolyte may be provided to exhibit a transmittance of 25 to 40% for visible light of 500 to 800 nm as measured by a UV-vis spectrophotometer.

[0014] The above GQD may be provided with an average particle size of 1 nm to 10 nm.

[0015] The oxide-based solid electrolyte may be provided by including at least one selected from the group consisting of lithium perovskite materials, lithium super-ionic conductors (LISICON), lithium garnet materials, or mixtures thereof.

[0016] The above oxide-based solid electrolyte may be provided including LLZO.

[0017] A solid-state battery according to another embodiment may be provided to include a solid electrolyte.

[0018] The above-described all-solid-state battery may be provided by including a positive electrode layer comprising a lithium metal oxide, a negative electrode layer that intercalates and deintercalates lithium ions, and a solid electrolyte interposed between the positive electrode layer and the negative electrode layer.

[0019] The above all-solid-state battery may be provided with a transmittance of 10 to 35% for visible light of 400 to 700 nm as measured by a UV-vis spectrophotometer.

[0020] The above all-solid-state battery may be provided with a transmittance of 20 to 40% for visible light of 500 to 800 nm as measured by a UV-vis spectrophotometer.

[0021] The above anode layer may be provided by including a current collector layer comprising silver nanowires (Ag NW) and an anode active material layer comprising lithium metal oxide.

[0022] The above cathode layer may be provided by including a substrate layer comprising at least one of PET (polyethylene terephthalate), glass, and PDMS, and a cathode active material layer provided on the substrate layer and comprising silicon nanowires (Si NW).

[0023] A method for manufacturing an all-solid-state battery according to another embodiment may be provided by including the steps of: preparing a positive electrode layer; preparing a negative electrode layer; and forming a solid electrolyte between the positive electrode layer and the negative electrode layer.

[0024] The step of forming the solid electrolyte may be provided by including the step of doping a dopant into an oxide-based solid electrolyte and sintering it, and the step of densifying the doped oxide-based solid electrolyte.

[0025] The step of preparing the anode layer may include a step of co-precipitating an anode active material precursor; a mechanical activation process step and a thermal activation process step.

[0026] The step of preparing the above cathode layer may include a step of mixing a cathode active material; a mechanical activation process step and a thermal activation process step. Effects of the invention

[0027] The solid electrolyte and all-solid-state battery according to one embodiment of the present invention have the effect of improving ion conductivity through doping of a dopant into the solid electrolyte.

[0028] A solid electrolyte and an all-solid-state battery according to one embodiment of the present invention can be utilized in various fields by securing a transmittance of visible light above a certain level.

[0029] The solid electrolyte and all-solid-state battery according to one embodiment of the present invention have flexible properties, so they can be utilized in various fields.

[0030] The solid electrolyte and all-solid-state battery according to one embodiment of the present invention can produce high-density pellets in a short sintering reaction time and have an effect advantageous to the mass production process. Brief explanation of the drawing

[0031] FIG. 1 schematically illustrates a solid electrolyte according to one embodiment of the present invention. FIG. 2 schematically illustrates an all-solid-state battery according to one embodiment of the present invention. FIG. 3 schematically illustrates an all-solid-state battery according to one embodiment of the present invention. FIG. 4 is a flowchart of a method for manufacturing an all-solid-state battery according to one embodiment of the present invention. FIG. 5 is a flowchart of the step of preparing a positive electrode layer in a method for manufacturing an all-solid-state battery according to one embodiment of the present invention. FIG. 6 is a flowchart of the step of preparing a negative electrode layer in a method for manufacturing an all-solid-state battery according to one embodiment of the present invention. FIG. 7 is a flowchart of the step of forming a solid electrolyte in a method for manufacturing an all-solid-state battery according to one embodiment of the present invention. Figure 8 shows a cross-sectional SEM image of a pellet of a solid electrolyte according to one embodiment of the present invention. Figure 9(a) shows the phase composition of LLZO pellets prepared by GQD doping according to Li concentration when the GQD concentration is 10 wt% and 20 wt%, analyzed by XRD, and Figure 9(b) shows the Li concentration of LLZO prepared by GQD doping according to initial Li content, analyzed by ICP-AES. Figure 10 shows the EIS curves of LLZO pellets prepared by GQD doping according to initial Li concentration when the GQD concentration is 10 wt% and 20 wt%. Figure 11(a) is a curve showing the transmittance of GQD-doped LLZO according to wavelength when the GQD concentration is 10 wt% and 20 wt%, and Figure 11(b) is a curve showing the transmittance of LLZO according to GQD doping concentration with additionally applied NCM nanoparticles. Figure 12(a) is a curve showing the transmittance according to wavelength of a sample with Ag NWs and NCM nanoparticles additionally applied to GQD-doped LLZO when the GQD concentration is 10 wt% and 20 wt%, and Figure 12(b) is a curve showing the transmittance according to wavelength of a sample with Ag NWs and NCM nanoparticles additionally applied to GQD-doped LLZO according to the GQD doping size. FIG. 13 shows the transparency of an all-solid-state battery according to one embodiment of the present invention under visible light. Specific details for implementing the invention

[0032] Throughout the specification, the same reference numerals refer to the same components. This specification does not describe all elements of the embodiments, and general content in the art to which the invention pertains or content that overlaps between embodiments is omitted.

[0033] Throughout the specification, when a part is described as being "connected" to another part, this includes not only cases where they are directly connected but also cases where they are indirectly connected, and indirect connections include connections made via a wireless communication network.

[0034] Furthermore, when it is stated that a part "includes" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0035] Singular expressions include plural expressions unless there is an obvious exception in the context.

[0036] In addition, terms such as "~part," "~unit," "~block," "~part," and "~module" may refer to a unit that processes at least one function or operation. For example, the above terms may refer to at least one piece of hardware such as an FPGA (field-programmable gate array) or ASIC (application specific integrated circuit), at least one piece of software stored in memory, or at least one process processed by a processor.

[0037] The symbols attached to each step are used to identify each step and do not indicate the order of the steps relative to one another; the steps may be performed differently from the specified order unless a specific order is clearly indicated in the context.

[0038] Hereinafter, embodiments relating to a solid electrolyte according to one aspect and a secondary battery including the same will be described in detail with reference to the attached drawings. The embodiments described in this specification and the configurations illustrated in the drawings are merely the most preferred embodiments of the present invention, and various equivalents and modifications that can replace them may exist at the time of filing this application.

[0039] Solid Electrolyte

[0040] FIG. 1 schematically illustrates a solid electrolyte according to one embodiment of the present invention.

[0041] As illustrated in FIG. 1, the solid electrolyte (10) may include an oxide-based solid electrolyte (11) and a dopant (12) doped into the oxide-based solid electrolyte (11).

[0042] The oxide-based solid electrolyte (11) may be configured to include at least one selected from the group consisting of lithium perovskite materials, lithium super-ionic conductors (LISICON) and lithium garnet materials or mixtures thereof.

[0043] More specifically, the oxide-based solid electrolyte (11) may include an LLZO-based compound which is a lithium garnet material, and the LLZO-based compound is a compound containing Li, La, Zr, and O, and may be Li7La3Zr2O12.

[0044] Here, the oxide-based solid electrolyte (11) may be doped with a dopant (12) to increase ionic conductivity and prevent the formation of a tetragonal phase. For example, the LLZO compound may be prepared in the form of a cubic garnet by cation substitution of the dopant (12).

[0045] The average particle size of the oxide-based solid electrolyte (11) after sintering can be 1 to 300 nm, and preferably 10 to 200 nm, 10 to 100 nm, or 25 nm to 75 nm. The average particle size of the LLZO-based compound of the oxide-based solid electrolyte (11) can be 1 nm to 150 nm, 10 nm to 100 nm, or 50 to 100 nm.

[0046] The dopant (12) may include at least one of GQD (Graphene Quantum Dot), Fe, Ta, Al, Ga, Nb, and Te. Preferably, the dopant may include GQD (Graphene Quantum Dot), and the dopant may consist only of GQD (Graphene Quantum Dot).

[0047] The dopant (12) may be included in an amount of 5% to 30% by weight based on the total weight of the oxide-based solid electrolyte (11), more specifically in an amount of 5% to 20% by weight, and preferably in an amount of 5% to 15% by weight.

[0048] The dopant (12) may be included in an amount of 5% to 30% by weight based on the total weight of the LLZO compound, more specifically in an amount of 5% to 20% by weight, and preferably in an amount of 5% to 15% by weight or 10% by weight.

[0049] The particle size of the dopant (12) can be provided to be 0.1 nm to 50 nm, 1 nm to 30 nm, and preferably 5 nm to 20 nm. In particular, the average particle size of the GQD among the dopant (12) can be provided to be 1 nm to 100 nm, and preferably 5 nm to 10 nm.

[0050] The solid electrolyte (10) according to the present invention exhibits a visible light transmittance of 18 to 40% or less. Specifically, within the wavelength range of visible light detectable by the human eye, which is 400 nm to 700 nm, the solid electrolyte (10) according to the present invention is provided with a transmittance of 18 to 38%, and within 500 nm to 800 nm, it exhibits a transmittance of 25 to 40%.

[0051] Accordingly, the solid electrolyte (10) according to the present invention can exhibit a certain level of transparency to visible light and can be applied to the all-solid-state battery (1) described later to produce a transparent all-solid-state battery.

[0052] Solid-state battery

[0053] FIGS. 2 and FIGS. 3 schematically illustrate an all-solid-state battery according to one embodiment of the present invention.

[0054] As illustrated in FIGS. 2 and 3, a solid electrolyte (10) is interposed between a positive electrode layer (20) and a negative electrode layer (30) in the all-solid-state battery (1). At this time, the solid electrolyte (10) may be provided in close contact with the positive electrode layer (20) and the negative electrode layer (30) for ion conductivity.

[0055] The positive layer (20) has a structure in which a positive active material layer (22) is formed on a positive current collector (21). Here, the positive active material layer (22) includes electrode materials such as a positive active material, a conductive material, and a binder.

[0056] The positive current collector (21) is conductive, for example, the positive current collector (21) may be made of stainless steel, aluminum, nickel, silver, and Ag nanowire. Preferably, the positive current collector (21) may be made of Ag nanowire with a nano-scale thickness to improve the visible light transmittance of the all-solid-state battery. In this case, when the positive current collector (21) is made of Ag nanowire, the thickness of the positive current collector (21) may be 500 nm or less, or 100 nm or less, or 50 nm or less, and the diameter of the Ag nanowire may be 1 nm to 100 nm, or 5 nm to 50 nm, or 10 nm to 30 nm. Preferably, the positive current collector (21) may be made of Ag nanowire with a diameter of 10 nm and a thickness of 20 nm.

[0057] The positive electrode active material is a compound capable of reversibly intercalating and deintercalating lithium ions. Specifically, it may include a lithium metal oxide containing lithium and one or more metals such as cobalt, manganese, nickel, or aluminum. For example, the lithium metal oxide may include a lithium-manganese oxide, a lithium-cobalt oxide, a lithium-nickel oxide, a lithium-cobalt-nickel oxide, a lithium-nickel-manganese-cobalt oxide, and a lithium iron phosphate oxide.

[0058] The cathode active material can be prepared by extracting the powder by spray drying after a co-precipitation reaction of NiSO4, CoSO4, MnSO4, NH4OH, and NaOH, followed by performing a mechanical activation process through zirconia ball milling and a high energy thermal activation process (pre-heating 300~400℃ for 1~8h in air, calcination 500~600℃ for 1~8h in air).

[0059] Preferably, the positive active material may be provided as a lithium-cobalt-nickel or lithium-nickel-manganese-cobalt oxide with a nanoscale thickness to improve the visible light transmittance of the all-solid-state battery. At this time, the thickness of the positive active material layer (22) may be provided as 1 nm to 1000 nm, or 10 nm to 500 nm, or 50 nm to 200 nm, and the particle size of the positive active material may be provided as 0.1 nm to 100 nm, or 1 nm to 70 nm, or 10 nm to 50 nm.

[0060] The positive active material may be included in an amount of 60 to 99 weight%, or 70 to 99 weight%, preferably 80 to 98 weight%, based on the total weight of the positive active material layer (22).

[0061] The conductive material improves the conductivity of the cathode active material, and for example, conductive materials such as carbon powders such as GQD, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black, and conductive fibers such as carbon fibers or metal fibers may be used. Preferably, the conductive material may be provided as GQD with a diameter of 5 to 50 nm.

[0062] The conductive material may be included in an amount of 0.1 to 10 weight%, or 0.5 to 5 weight%, preferably 0.5 to 3 weight%, based on the total weight of the positive active material layer (22).

[0063] The binder is used to bond the conductive material, the positive active material, and the current collector (21), and materials such as polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethylcellulose (CMC), styrene-butadiene rubber, and fluororubber may be used.

[0064] The binder may be included in an amount of 0.5 to 10 weight%, or 0.5 to 5 weight%, preferably 0.5 to 3 weight%, based on the total weight of the positive active material layer (22).

[0065] The negative electrode layer (30) has a structure in which a negative electrode active material layer (32) is formed on a negative electrode current collector (31). Here, the negative electrode active material layer (32) includes electrode materials such as a negative electrode active material, a conductive material, and a binder.

[0066] The negative current collector (31) may be conductive and is not particularly limited. Preferably, the negative current collector (31) may be made of Cu nanowire, and the Cu nanowire may be made to satisfy a diameter of 1 nm to 100 nm or 10 nm to 30 nm and a thickness of 100 nm or less or 50 nm or less.

[0067] The negative electrode active material is a compound capable of reversibly intercalating and deintercalating lithium ions. Specifically, it can be provided with carbon materials, metals, lithium alloys, metal composite oxides, etc., and more specifically, it may include crystalline carbon, amorphous carbon, natural graphite, artificial graphite, silicon, lithium, GQD, and Si nanowires.

[0068] The cathode active material can be prepared as GQD / Si NW / C cathode active material nanoparticles by mixing GQD, Si nanowire, and carbon dot, and performing a mechanical activation process through zirconia ball milling and a high energy thermal activation process (pre-heating 300~400℃ for 1~8h in air, calcination 500~600℃ for 1~8h in air).

[0069] Preferably, the negative electrode active material layer (32) is 1 to improve the visible light transmittance of the all-solid-state battery. The thickness may be provided as follows. The thickness of the negative electrode active material layer (32) may be provided as 1 nm to 1000 nm, or 5 nm to 500 nm, or 10 nm to 100 nm or less, and the particle size of the positive electrode active material may be provided as 0.1 nm to 100 nm, or 1 nm to 70 nm, or 10 nm to 50 nm.

[0070] The negative active material layer (32) further includes a conductive material and a binder.

[0071] The conductive material improves the conductivity of the cathode active material, and for example, conductive materials such as carbon powders such as GQD, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black, and conductive fibers such as carbon fibers or metal fibers may be used. Preferably, the conductive material may be provided as GQD with a diameter of 5 to 50 nm.

[0072] The conductive material may be included in an amount of 0.1 to 10 weight%, or 0.5 to 5 weight%, preferably 0.5 to 3 weight%, based on the total weight of the negative electrode active material layer (32).

[0073] The binder is used to bond the conductive material, the positive active material, and the current collector (21), and materials such as polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethylcellulose (CMC), styrene-butadiene rubber, and fluororubber may be used.

[0074] The binder may be included in an amount of 0.5 to 10 weight% or 0.5 to 5 weight%, preferably 0.5 to 3 weight% or 0.1 to 10 g based on the total weight of the positive active material layer (22).

[0075] A solid electrolyte is interposed between the anode layer (20) and the cathode layer (30) to transfer lithium ions between the anode layer (20) and the cathode layer (30) during charging and discharging. Since the details are the same as those described above, the description is omitted.

[0076] The all-solid-state battery according to the present invention exhibits a visible light transmittance of 10 to 40% or less. Specifically, within the wavelength range of visible light detectable by the human eye, which is 400 nm to 700 nm, the solid electrolyte according to the present invention is provided with a transmittance of 10 to 35%, and exhibits a transmittance of 20 to 40% in the range of 500 nm to 800 nm.

[0077] Hereinafter, a method for manufacturing an all-solid-state battery according to one embodiment of the present invention will be described.

[0078] FIGS. 4 to 7 are flowcharts of a method for manufacturing an all-solid-state battery according to an embodiment of the present invention.

[0079] Referring to FIGS. 4 to 7, a method for manufacturing an all-solid-state battery (S1) according to one embodiment of the present invention may include the steps of preparing a positive electrode layer (S10), preparing a negative electrode layer (S20), and forming a solid electrolyte between the positive electrode layer and the negative electrode layer (S30).

[0080] The step of preparing the anode layer (S10) may include a step of co-precipitating an anode active material precursor (S11), a mechanical activation process step (S12), and a thermal activation process step (S13).

[0081] The step of co-precipitating the cathode active material precursor (S11) is a step of co-precipitating NiSO4, CoSO4, MnSO4, NH4OH, and NaOH. However, the types of cathode active materials and precursors of the present invention are not limited thereto, and various modifications are possible as long as they are materials capable of reversibly intercalating and deintercalating lithium ions. Additionally, after this step, a step of extracting the material obtained by spray drying to form a powder may be included.

[0082] The mechanical activation process step (S12) is a zirconia ball milling step in which the material is ground or processed using zirconia (ZrO2) balls.

[0083] The thermal activation process step (S13) is a process of thermally activating energy in a heat treatment temperature range of 200 to 600°C. Here, the preheating process can be carried out at 300 to 400°C for 1 to 8 hours, and the firing process can be carried out at 500 to 600°C for 1 to 8 hours.

[0084] The step of preparing the cathode layer (S20) may include a step of mixing the cathode active material (S21), a mechanical activation process step (S22), and a thermal activation process step (S23).

[0085] The step of mixing the negative electrode active material (S21) is a step of mixing GQD, Si nanowire, and carbon dot as the negative electrode active material. However, the type of negative electrode active material of the present invention is not limited thereto, and various modifications are possible as long as the material is capable of reversibly intercalating and deintercalating lithium ions.

[0086] The mechanical activation process step (S22) is a zirconia ball milling step in which the material is ground or processed using zirconia (ZrO2) balls.

[0087] The thermal activation process step (S23) is a process of thermally activating energy in a heat treatment temperature range of 200 to 600°C. Here, the preheating process can be carried out at 300 to 400°C for 1 to 8 hours, and the firing process can be carried out at 500 to 600°C for 1 to 8 hours.

[0088] The step of forming a solid electrolyte (S30) may include a step of doping a dopant into an oxide-based solid electrolyte and sintering it (S31), and a step of densifying the doped oxide-based solid electrolyte (S32).

[0089] The step (S31) of doping a dopant into an oxide-based solid electrolyte and sintering it may include mixing Li2CO3, La2O2, and ZrO2, ball milling the mixture, and then performing heat treatment at 200 to 600°C for 1 to 8 hours. During this process, the heat treatment and ball milling may be repeated several times, and the oxide-based solid electrolyte may be sintered into a pellet form. At this time, a dopant may be doped into the oxide-based solid electrolyte during the heat treatment process, and the dopant may be provided in an amount of 10 wt% to 20 wt% of the oxide-based solid electrolyte and may include GQD.

[0090] The step of densifying the doped oxide-based solid electrolyte (S32) is a step of densifying the heat-treated oxide-based solid electrolyte into a pellet-shaped solid electrolyte using a sintering method.

[0091] The step (S30) of forming a solid electrolyte can be manufactured as a separate solid electrolyte through the process described above, and can be formed between the anode layer and the cathode layer by applying pressure after being interposed between the anode layer and the cathode layer.

[0092] The present invention will be explained in more detail below through specific embodiments. However, the following embodiments are merely examples to aid in understanding the invention and do not limit the scope of the invention. It is obvious to those skilled in the art that various changes and modifications are possible within the scope and spirit of this description.

[0093] <Example 1>

[0094] Solid electrolyte manufacturing process

[0095] An LLZO solid electrolyte doped with 10 wt% GQD was fabricated using a solid reaction synthesis method. The initial raw materials, Li2CO₃, LaO₃, and ZrO₂, were prepared with high purity and dispersed in an isopropyl alcohol solvent, followed by a ball milling process. The molar ratio of Li:La:Zr was set to x:3:2 (x=6.5, 7.5, 8.5), and ball milling was performed at 300 rpm for 3 hours. A second milling was carried out at 500 rpm for 4 hours, followed by a two-stage continuous heat treatment at 400°C for 1 hour and 500°C for 6 hours. Subsequently, a third ball milling was performed at 600 rpm for 2 hours, and the powder was calcined at 550°C for 8 hours. The calcined powder was re-grinded at various rotational speeds (200, 300, 400, and 500 rpm) for 2 hours and compressed into pellets at 50–150 MPa. During the heat treatment process, the LLZO solid electrolyte and GQD can be mixed at 10 wt% and heat-treated together. The pellets obtained at this time were placed in an MgO crucible covered with the same mother powder and sintered at 550°C for 60 minutes. Finally, to minimize powder aggregation, the LLZO solid solution was ball-milled at 300 rpm for 15 minutes.

[0096] The structure and microstructure of the sintered pellets were evaluated through XRD and SEM analysis, and the average particle size was determined through this evaluation.

[0097] In addition, after depositing Au electrodes on both sides using PVD (Physical vapor deposition) technology, ionic conductivity was measured with an impedance spectrometer (Biologic, SP 200) in the frequency range of 1 kHz to 10 MHz with an amplitude of 10 mV. Measurements were performed in a vacuum oven at temperatures ranging from 25 to 80°C.

[0098] Densification of the pellets was achieved by SPS (GT Advanced Technologies Inc., SPS 10-4). This was performed by loading the synthesized powder into a 10 mm diameter graphene die lined with graphene sheets. The assembly was placed in a vacuum chamber and heated to 400°C while simultaneously applying pressure. The temperature was maintained constant for 15 minutes to reach thermal equilibrium across the entire sample, then increased to 450°C by applying a heating rate of 20°C min⁻¹. Pressure was continuously increased until it reached 50 MPa, and the pressure was released after a residence time of 15 minutes. The temperature profile was controlled at a cooling rate of 100°C min⁻¹. High-density pellets with a thickness of 5 mm were produced through a sintering process.

[0099] Referring to Figure 8, at the optimized GQD concentration (10 wt%), all GQD-doped LLZO pellets exhibited a smooth surface with small closed pores, whereas more grain boundaries were observed in samples with very low GQD content or larger GQD sizes of 20 nanometers or more. Additionally, no crystal defects accompanied by cracks were observed in the LLZO pellets, which is generally observed under good sintering conditions of ceramics. It was confirmed that samples with a GQD concentration of 10 wt% and a GQD size of 5 nanometers were well sintered at high density, which can lead to low grain boundary resistance and consequently improve the ionic conductivity of these pellets. In contrast, samples with GQD concentrations lower than 5 wt% or higher than 30 wt% exhibited many grain boundaries and defects, which contribute to lower ionic conductivity. Therefore, it can be seen that an appropriate initial GQD concentration is important to ensure excellent sintering conditions for LLZO pellets.

[0100] Solid-state battery manufacturing process

[0101] The anode layer was prepared by forming a current collector and an anode active material layer. The anode current collector consists of Ag nanowires with a diameter of 10 nm and was manufactured to a thickness of 20 nm or less. The anode active material layer is coated on the anode current collector; it is prepared with an average particle size of 10 nm and a thickness of 50 nm or less by co-precipitating NiSO4, CoSO4, MnSO4, NH4OH, and NaOH, followed by spray drying to extract the powder, and then performing a mechanical activation process via zirconia ball milling and a high-energy thermal activation process (pre-heating 400℃ for 2h in air, calcination 500℃ for 2h in air). At this time, 2 g of PVDF (Polyvinylidene Fluoride) was included as a binder, and a small amount of 5 nm GQD was included as a conductive material.

[0102] The cathode layer was prepared as a current collector and a cathode active material layer. The cathode current collector consists of Cu nanowires with a diameter of 10 nm and was manufactured with a thickness of 20 nm or less. The cathode active material layer is coated on the cathode current collector and is prepared with an average particle size of 10 nm and a thickness of 50 nm or less by mixing GQD, Si nanowire, and carbon dots, and performing a mechanical activation process via zirconia ball milling and a high-energy thermal activation process (pre-heating 400℃ for 2h in air, calcination 500℃ for 8h in air). At this time, 2 g of PVDF (Polyvinylidene Fluoride) was included as a binder, and a small amount of 5 nm GQD was included as a conductive material.

[0103] The solid electrolyte was prepared according to the solid electrolyte fabrication process described earlier.

[0104] The anode layer, cathode layer, and solid electrolyte are manufactured by the method described above, and the solid electrolyte can be interposed between the anode layer and the cathode layer and pressurized.

[0105] <Example 2>

[0106] Solid electrolyte manufacturing process

[0107] An LLZO solid electrolyte was prepared by doping GQD at 20 wt% using the same method as the 10 wt% doped pellet, and was prepared in the same way as Example 1 except for this.

[0108] Solid-state battery manufacturing process

[0109] It was manufactured in the same manner as Example 1, except for the solid electrolyte.

[0111] The characteristics of the solid electrolyte and all-solid-state battery of the present invention will be described below.

[0112] Figure 9(a) shows the phase composition of LLZO pellets prepared by GQD doping according to Li concentration when the GQD concentration is 10 wt% and 20 wt%, analyzed by XRD, and Figure 9(b) shows the Li concentration of LLZO prepared by GQD doping according to initial Li content, analyzed by ICP-AES.

[0113] Referring to Fig. 9(a), even at low GQD content, the cubic phase formation of GQD-doped LLZO can be reduced due to secondary phases. LLZO with a GQD concentration of 10 wt% exhibited a relatively higher cubic phase content compared to LLZO with a GQD concentration of 20 wt%. When the initial GQD concentration was increased to 5 wt% or more, a mono-doped LLZO structure was formed. Furthermore, the GQD-doped LLZO structure promotes better cubic phase stability after pellet sintering. XRD Rietveld purification analysis results showed that when the GQD concentration increased from 10 wt% to 20 wt%, the cubic phase ratio of LLZO increased from 62% to over 70%. Conversely, when the GQD concentration increased from 10 wt% to 20 wt%, the cubic phase ratio of LLZO decreased from 88% to 72%. The highest cubic ratio was observed when the GQD concentration was 10 wt%, indicating that it is optimized when combined with GQD doping. Thus, it can be seen that LLZO powder and pellets improve cubic formation and stability through GQD doping.

[0114] Referring to Fig. 9(b), the lower Li concentration observed in the 10wt% GQD-doped LLZO powder compared to the 20wt% GQD-doped LLZO powders with initial Li contents of 6.5 and 7.5 mol can be attributed to the effective replacement of Li sites by an appropriate amount of GQD. The 10wt% GQD-doped LLZO structure showed a smaller rate of change in Li content than the structure with a higher GQD content. This suggests that GQD acted as an efficient protective layer on the Li sites of the LLZO structure after calcination by introducing doping into the LLZO powders prepared with the aforementioned 5–20wt% GQD concentrations.

[0115] Figure 10 shows the EIS curves of LLZO pellets prepared by GQD doping according to initial Li concentration when the GQD concentration is 10 wt% and 20 wt%.

[0116] Referring to Fig. 10, the Grain Boundary impedance semicircles according to changes in terminal frequency showed a much lower diameter than the other curves at the initial values. In the high-frequency region of the Nyquist plot, the two semicircle curves corresponding to 10–20 wt% GQD concentration and GQD doping correspond to the Grain Boundary resistance according to terminal frequency, respectively. The spread tails at mid and low frequencies correspond to the Warburg impedance.

[0117] For each doping type, the pellet with an initial Li concentration of 7.5 mol exhibited the highest conductivity value due to a high concentration conductive phase (cubic LLZO) without a secondary phase. Despite the high proportion of the cubic phase in the structure, the sample at low Li content (x = 6.5) showed lower Li ion conductivity than the sample with the optimized Li concentration (x = 7.5) due to the presence of La. As the Li content increased to 8.5 mol, the ion conductivity decreased as the tetragonal structure became dominant in the crystal structure of the pellet due to a phase transition. In particular, the 10 wt% GQD transition metal-doped LLZO structure sample showed the best ion conductivity (2.2 x 10⁻⁴ S cm⁻¹), whereas the ion conductivity of the 20 wt% GQD-doped LLZO sample was approximately 1.3 x 10⁻⁴ S cm⁻¹. Therefore, it can be seen that the structure of 10 wt% GQD-doped LLZO plays an important role in improving lithium ion conductivity.

[0118] Figure 11(a) is a curve showing the transmittance of GQD-doped LLZO according to wavelength when the GQD concentration is 10 wt% and 20 wt%, and Figure 11(b) is a curve showing the transmittance of LLZO according to GQD doping concentration with additionally applied NCM nanoparticles.

[0119] Referring to Figures 11(a) and (b), the GQD-doped LLZO pellets measured by a UV-vis spectrophotometer showed a transmittance of 30–38% for visible light at 500–800 nm. The transmittance value of the NCM / GQD / LLZO pellets was 30–35% at 500 nm, which was similar to the transmittance before NCM nanoparticle coating.

[0120] Figure 12(a) is a curve showing the transmittance according to wavelength of a sample with Ag NWs and NCM nanoparticles additionally applied to GQD-doped LLZO when the GQD concentration is 10 wt% and 20 wt%, and Figure 12(b) is a curve showing the transmittance according to wavelength of a sample with Ag NWs and NCM nanoparticles additionally applied to GQD-doped LLZO according to the GQD doping size.

[0121] Referring to Figures 12(a) and (b), the Ag NW / NCM / GQD / LLZO pellets exhibited a transmittance of 26–32% for visible light at 500–800 nm. The transmittance of the Ag NW / NCM / GQD / LLZO pellets was 22–27% at 500 nm, which is similar to the transmittance before Ag NW coating.

[0122] FIG. 13 shows the transparency of an all-solid-state battery according to one embodiment of the present invention under visible light.

[0123] Referring to FIG. 13, it can be seen that the all-solid-state battery according to one embodiment of the present invention has a certain level of transmittance, so that the text on the back of the all-solid-state battery is transparent enough to be distinguished with the naked eye. In addition, it can be seen that the all-solid-state battery according to one embodiment of the present invention has flexible properties.

[0124] As described above, the disclosed embodiments have been explained with reference to the attached drawings. Those skilled in the art will understand that the present invention may be practiced in forms different from the disclosed embodiments without changing the technical spirit or essential features of the invention. The disclosed embodiments are illustrative and should not be interpreted restrictively. Explanation of the symbols

[0125] 1: Solid-state battery 10: Solid electrolyte 11: Oxide-based solid electrolytes 12: Dopant 20: Anode layer 21: Positive current collector 22: Positive active material layer 30: Cathode layer 31: Cathode current collector 32: Cathode active material layer

Claims

Claim 1 A solid electrolyte comprising an oxide-based solid electrolyte; and a dopant doped into the oxide-based solid electrolyte, wherein the dopant comprises GQD (Graphene Quantum Dot), and the oxide-based solid electrolyte is formed into a cubic garnet structure by the dopant. Claim 2 A solid electrolyte according to claim 1, characterized in that the dopant is 5% by weight or more and less than 20% by weight with respect to 100 parts by weight of the oxide-based solid electrolyte. Claim 3 In claim 1, the solid electrolyte is a solid electrolyte that exhibits a transmittance of 18 to 38% for visible light of 400 to 700 nm as measured by a UV-vis spectrophotometer. Claim 4 In claim 1, the solid electrolyte is a solid electrolyte that exhibits a transmittance of 25 to 40% for visible light of 500 to 800 nm as measured by a UV-vis spectrophotometer. Claim 5 In claim 1, the GQD is a solid electrolyte having an average particle size of 1 nm to 10 nm. Claim 6 In paragraph 2, the oxide-based solid electrolyte comprises at least one selected from the group consisting of lithium perovskite materials, lithium super-ionic conductors (LISICON), lithium garnet materials, or mixtures thereof. Claim 7 In paragraph 2, the oxide-based solid electrolyte is a solid electrolyte containing LLZO. Claim 8 An all-solid-state battery comprising a solid electrolyte according to any one of claims 1 to 7. Claim 9 In claim 8, the all-solid-state battery comprises a positive electrode layer containing a lithium metal oxide, a negative electrode layer that intercalates and deintercalates lithium ions, and a solid electrolyte interposed between the positive electrode layer and the negative electrode layer. Claim 10 In claim 9, the all-solid-state battery exhibits a transmittance of 10 to 35% for visible light of 400 to 700 nm as measured by a UV-vis spectrophotometer. Claim 11 In claim 9, the all-solid-state battery is an all-solid-state battery that exhibits a transmittance of 20 to 40% for visible light of 500 to 800 nm as measured by a UV-vis spectrophotometer. Claim 12 In claim 9, the anode layer comprises a current collector layer comprising nanowires (Ag NW) and an anode active material layer comprising lithium metal oxide, in an all-solid-state battery. Claim 13 In claim 12, the all-solid-state battery comprises a negative electrode layer comprising at least one of PET (polyethylene terephthalate), glass, and PDMS, and a negative electrode active material layer provided on the substrate layer and comprising silicon nanowires (Si NW). Claim 14 A method for manufacturing an all-solid-state battery according to claim 9, comprising the steps of: preparing a positive electrode layer; preparing a negative electrode layer; and forming a solid electrolyte between the positive electrode layer and the negative electrode layer. Claim 15 A method for manufacturing an all-solid-state battery according to claim 14, wherein the step of forming the solid electrolyte comprises: a step of doping a dopant into an oxide-based solid electrolyte and sintering it; and a step of densifying the doped oxide-based solid electrolyte. Claim 16 In claim 14, the step of preparing the anode layer comprises a step of co-precipitating an anode active material precursor; a mechanical activation process step; and a thermal activation process step, in a method for manufacturing an all-solid-state battery. Claim 17 In claim 14, the step of preparing the negative electrode layer comprises a step of mixing a negative electrode active material; a mechanical activation process step; and a thermal activation process step, in a method for manufacturing an all-solid-state battery.

Citation Information

Patent Citations

  • Bipolar battery

    JP2012216561A

  • Electrochemical devices containing carbon quantum dot ionic compound electrolytes

    JP2020521310A

  • Solid-state electrolyte, all-solid-state lithium battery and its manufacturing method

    KR102493809B1